Self-driven solutions and resilience adapted by people with drug-resistant tuberculosis and their caregivers in Bengaluru and Hyderabad, India: a qualitative studyResearch in context - Karikalan Nagarajan; Karthikeyan Kumarswamy; Rehana Begum; Vikas Panibatla; Anil Singarajipura; Rajesham Adepu; Joseph Francis Munjattu; Senthil Sellapan; Stephen Arangba; Amrita Goswami; Reuben Swamickan; Javeed Basha; et al. (Elsevier, 2024)
Summary: Background: One-fifth of people with drug-resistance tuberculosis (DR-TB) who were initiated on newer shorter treatment regimen (with injection) had unfavourable treatment outcomes in India as on 2020. Evidence on self-driven solutions and resilience adapted by people with DR-TB (PwDR-TB) towards their multi-dimensional disease and treatment challenges are scarce globally, which we aimed to understand. Methods: In this qualitative study using positive deviance framework, we conducted semi-structured in-depth interviews among consenting adult PwDR-TB (7 women, 13 men) who completed shorter treatment regimen (including injections) with maximum treatment adherence. The study was conducted in the southern districts of Bengaluru and Hyderabad, India between June 2020 and December 2022. Caregivers (14 women, 6 men) and health providers (8 men, 2 women) of PwDR-TB were also interviewed. Interviews were conducted in local language (Kannada, Tamil, Telugu, Urdu and Hindi) and inquired about practices, behaviours, experiences, perceptions and attributes which enabled maximum adherence and resilience of PwDR-TB. Interviews were audio recorded, transcribed, and translated to English and coded for thematic analysis using inductive approach. Findings: Distinctive themes explanatory of the self-driven solutions and resilience exhibited by PwDR-TB and their caregivers were identified: (i) Self-adaptation towards the biological consequences of drugs, by personalised nutritional and adjuvant practices, which helped to improve drug ingestion and therapeutic effects. Also home remedies and self-plans for ameliorating injection pain. (ii) Perceptual adaptation towards drugs aversion and fatigue, by their mind diversion practices, routinisation and normalisation of drug intake process. and constant reinforcement and re-interpretation of bodily signs of disease recovery (iii) Family caregivers intense and participatory care for PwDR-TB, by aiding their essential life activities and ensuring survival, learning and fulfilling special nutritional needs and goal oriented actions to aid drug intake (iv) Health care providers care, marked by swift and timely risk mitigation of side-effects and crisis response (v) Acquired self-efficacy of PwDR-TB, by their decisive family concerns resulting in attitudinal change. Also being sensitised on the detrimental consequences of disease and being motivated through positive examples. Interpretation: Synthesised findings on self-driven solutions and resilience towards the multi-dimensional DR-TB challenges provides opportunity for developing and testing new interventions for its effectiveness in DR-TB care settings globally. Designing and testing personalised cognitive interventions for PwDR-TB: to inculcate attitudinal change and self-efficacy towards medication, developing cognitive reinforcements to address the perception burden of treatment, skill building and mainstreaming the role of family caregivers as therapeutic partners of PwDR-TB, curating self-adaptive behaviours and practices of PwDR-TB to normalise their drug consumptions experiences could be the way forward in building resilience towards DR-TB. Funding: United States Agency for International Development (USAID) through Karnataka Health Promotion Trust (KHPT), Bengaluru, India.